The Mediating Role of Hopelessness in the Relationship Between Social Media Addiction and Loneliness Among Adolescents - Durmus, Mustafa; Sarman, Abdullah; Ciftci, Necmettin; Durmus, Yusuf (Wiley, 2025)
Purpose This study aims to explore the mediating role of hopelessness in the relationship between social media addiction and loneliness among adolescents. Methods This study was conducted using a descriptive cross-sectional correlational design. The study population comprised high school students in a provincial center in eastern Turkey. Through cluster sampling, 946 adolescents were included. This study was conducted between May 2024 and Sep 2024. Data collection involved a personal information form, the Social Media Addiction Scale for Adolescents (SMAAS), the UCLA Loneliness Scale Short Form (ULS-8), and the Beck Hopelessness Scale (BHS). Data analysis was conducted using SPSS 25, G*Power 3.1, and AMOS 24 software. Results The mean scores were as follows: SMAAS (20.44 +/- 6.96), ULS-8 (16.14 +/- 3.97), and BHS (7.25 +/- 5.16). Significant positive correlations were found between the scales. The model describing the relationships among social media addiction, loneliness, and hopelessness was within acceptable limits and yielded significant results (Chi(2)/df=2.978, RMSEA = 0.052, CFI = 0.962, GFI = 0.971, IFI = 0.912). Social media addiction significantly affected loneliness, and time spent on social media also had a significant impact on loneliness (p < 0.001). Conclusions Adolescents were found to use social media extensively, mainly for communication with friends and family. Hopelessness and time spent on social media were identified as mediators in the relationship between social media addiction and loneliness. Findings suggest that reducing social media use may help mitigate loneliness and hopelessness. Mental health assessments should consider social media behavior, and educational programs should address its psychological impacts. Child and adolescent psychiatric nurses should be trained to recognize signs of loneliness and hopelessness in adolescents at an early stage.
Keywords: adolescent; hopelessness; loneliness; nursing; social media addiction